The Effect of Multidimensional Consumer Perceived Value on Customer Satisfaction and Purchase Intention of Organic Food - Ach Ainur Rohman; Rosihan Asmara; Dwi Retno Andriani (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2023)
The rapid and widespread growth of the organic food market is considered to become one of the largest growing markets in the food industry. The main objective of this research is to investigate and evaluate the effect of multidimensional consumer perceived value on customer satisfaction and purchase intention in the context of organic food. The data collection was carried out with 234 Indonesian consumers of organic food. The multidimensional consumer perceived value has been formed by 4 dimensions which include functional value, economic value, emotional value, and social value. consumer perceived value is considered to influence customer satisfaction and purchase intention. structural equation modeling (SEM-AMOS) was used to analyze the relationship between them. The result indicates that the consumer perceived value positively influences customer satisfaction and purchase intention. The consumer perceived value has no strong direct influence on purchase intention. Hence, the involvement of customer satisfaction is able to be a full mediator between the customer perceived value and purchase intention. This research contributes to reflecting consumer preferences of organic food in Indonesia as a developing country which is assessed by consumer perceived value, customer satisfaction, and purchase intention.